Various Silver Nanostructures on Sapphire Using Plasmon Self-Assembly and Dewetting of Thin Films - Kunwar, Sundar; Sui, Mao; Zhang, Quanzhen; Pandey, Puran; Li, Ming-Yu; Lee, Jihoon (Nano-Micro Letters, 2016)
Silver (Ag) nanostructures demonstrate outstanding optical, electrical, magnetic, and catalytic properties and are utilized in photonic, energy, sensors, and biomedical devices. The target application and the performance can be inherently tuned by control of configuration, shape, and size of Ag nanostructures. In this work, we demonstrate the systematical fabrication of various configurations of Ag nanostructures on sapphire (0001) by controlling the Ag deposition thickness at different annealing environments in a plasma ion coater. In particular, the evolution of Ag particles (between 2 and 20 nm), irregular nanoclusters (between 30 and 60 nm), and nanocluster networks (between 80 and 200 nm) are found be depended on the thickness of Ag thin film. The results were systematically analyzed and explained based on the solid-state dewetting, surface diffusion, Volmer–Weber growth model, coalescence, and surface energy minimization mechanism. The growth behavior of Ag nanostructures is remarkably differentiated at higher annealing temperature (750 °C) due to the sublimation and temperature-dependent characteristic of dewetting process. In addition, Raman and reflectance spectra analyses reveal that optical properties of Ag nanostructures depend on their morphology. Highlights: 1 Various configurations of Ag nanostructures were systematically fabricated on sapphire (0001) by controlling the deposition thickness and annealing environment in a plasma ion coater. 2 The results were systematically analyzed based on the solid-state dewetting, surface diffusion, Volmer-Weber growth model, coalescence and surface energy minimization mechanism.